An assessment of irrigated rice production energy efficiency and environmental footprint with rice straw management practices - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
IRRI participated in a comparative analysis to identify the environmental impact of contrasting straw management options on basis of the energy balance and productivity of rice farming. The research paper provides scientific evidences for improved rice straw management and is published as a journal article.